الاندماج ضمن سلاسل القيمة العالمية كآلية لدعم قطاع المؤسسات الصغيرة والمتوسطة في الجزائر - جديدي, روضة (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة الى طرح آلية حديثة يمكن للمؤسسات الصغيرة والمتوسطة من خلالها استغلال مؤهلاتها وقدراتها التنافسية وإيجاد فرص للاندماج في السوق الدولية عبر الانضمام الى سلاسل القيمة العالمية وزيادة صادراتها خاصة في القطاع الصناعي.واسفرت النتائج المتوصل اليها عن ان قطاع المؤسسات الصغيرة المتوسطة لا يرقى للمنافسة بسبب صغر حجم هذه المؤسسات وكون اغلبها ينشط في قطاع الخدمات.لكن تبقى المؤسسات العاملة في الصناعات الخفيفة مثل المواد الكيماوية وتكرير مشتقات النفط،منتجات المناجم،المنتجات الغذائية ......وغيرها تشكل فرصة امام هذا القطاع لتعزيز وجوده في السوق العالمية. This study aimed to present a modern mechanism through which small and medium enterprises can exploit their qualifications and competitive capabilities and find opportunities to integrate into the international market by joining global value chains and increasing their exports, especially in the industrial sector. The results obtained showed that the sector of small and medium enterprises is not up to competition due to the small size of these enterprises and the fact that most of them are active in the service sector. And others constitute an opportunity for this sector to enhance its presence in the global market
Integration within global value chains as a mechanism to support the SME sector in Algeria
مقال
Keywords: مؤسسات الصغيرة والمتوسطة.، سلسلة القيمة.، سلاسل القيمة العالمية، جزائر; Small and medium enterprises; value chain; global value chains; Algeria.